The Influence of Aluminium–Silicon Alloy on ZDDP Tribofilm Formation on the Counter-Surface - Shimizu,Y; Spikes,HA (Tribology Letters, 2017)
In order to reduce vehicle weight and thus improve fuel economy, aluminium (Al) alloys have been increasingly adopted as contact surfaces such as piston skirts and cylinder liners in current engines. In general, hypereutectic Al–Si alloys are used, in which hard silicon grains are embedded in a softer Al–Si single phase matrix. It is reported that after rubbing, the matrix is removed to leave silicon grains protruding from the surface. However, the response of the counter-surface by these silicon grains is rarely investigated. In this study, mini traction machine–space layer imaging (MTM–SLIM) has been used to monitor tribofilm formation in situ and investigate the evolution of both surfaces in the contact of a steel ball on an Al–Si disc lubricated by ZDDP solution. In low-load conditions, the top layer of aluminium on the Al–Si disc is removed physically to leave silicon grains protruding from the surface, while ZDDP tribofilm pads are formed mainly on the grains. On the counter-surface (steel ball), ZDDP tribofilms are formed and build up with no wear scars. In high-load conditions, deep gaps are observed to form initially round the silicon grains on the disc. During rubbing, these become shallower, while the silicon grains start to protrude. On the steel ball, ZDDP tribofilm is generated initially over the whole rubbing track, but then the tribofilm in the middle of the track is almost completely removed by rubbing against the protruding silicon grains. Wear of the underlying steel surface then ensues.